Equity Sensitivity as a Shield: Understanding Job Performance in the Face of Psychological Contract Breaches Among Indonesian Lecturers (Journal of Education Culture and Society, 2025)
Aim. This study examines how equity sensitivity moderates the relationship between psychological contract breach and job performance among Indonesian lecturers, with particular attention to demographic and institutional factors. It also investigates the impact of psychological contract dynamics on job performance in higher education.Methods. A cross-sectional survey of 155 Indonesian lecturers was analyzed using SmartPLS 4.0 for structural equation modelling. The model incorporated five control variables: age, tenure, gender, institution type, and education. Psychological contract breach, job performance, and equity sensitivity were measured using validated scales.Results. The results reveal equity sensitivity has a strong positive effect on job performance (β = 0.448, p < 0.001). Psychological contract breach shows an insignificant impact (β = 0.114, p = 0.160). Age positively influences job performance (β = 0.206, p = 0.048), and lecturers at public universities perform better than those at private institutions (β = -0.299, p = 0.025). Gender, education, and tenure do not significantly affect job performance. These results emphasize the equity sensitivity’s role and institutional factors in shaping job performance.Conclusion. The study suggests that psychological contract breach does not always hinder job performance, especially in Indonesia’s collectivist culture. Equity sensitivity plays a key role in sustaining performance despite unmet expectations. Universities should focus on fairness, resource allocation, and support systems to enhance lecturer performance.Research restrictions. The cross-sectional design restricts causal interpretation, warranting future longitudinal studies.Cognitive value. This is the first study to examine equity sensitivity’s moderating role in Indonesian higher education, providing new insights into psychological contracts and individual differences in non-Western academic settings.